The General Orthopaedist: Going the Way of the Dinosaur or the Next Subspecialty?. (18th July 2018) - Mulcahey, Mary K.; Kenter, Keith; Black, Kevin P.
Abstract : Abstract: Orthopaedic specialization has increased substantially over the past several decades, partly due to the desire of residents to improve their clinical expertise and to increase the likelihood that they will obtain a position with better compensation and a more balanced lifestyle. The American Academy of Orthopaedic Surgeons (AAOS) census data support this trend, demonstrating a substantial rise in the percentage of practicing orthopaedic surgeons who identify themselves as specialists rather than as general orthopaedic surgeons. There is a perception that a more narrowed scope of practice may prevent the current orthopaedic workforce from being able to adequately care for populations in rural areas of the United States. Additional consideration should be given to clearly defining the necessary knowledge and skills of a general orthopaedist in the twenty-first century, to understanding their role in musculoskeletal care, and to reevaluating residency educational experiences relative to their ability to prepare graduates to practice general orthopaedics independently.